Inhibitor development in previously treated hemophilia A patients: a systematic review, meta‐analysis, and meta‐regression. (12th September 2013) - Xi, M.; Makris, M.; Marcucci, M.; Santagostino, E.; Mannucci, P. M.; Iorio, A.
Summary Background The development of neutralizing alloantibodies (inhibitors) is the most serious complication of factor VIII (FVIII) replacement therapy in patients with hemophilia A. Unlike previously untreated patients, no definite risk factors for inhibitor development are known for previously treated patients (PTPs). The investigation of the development of inhibitors in PTPs is hindered by several methodological limitations in the available literature. We conducted a systematic review to account for these limitations. Methods We considered the studies reporting on PTPs that were included in the Wight and Paisley meta‐analysis and a systematic search of MEDLINE, EMBASE, and The Cochrane Library was conducted to identify studies published after 2003. Studies that investigated the development of inhibitors in hemophilia A PTPs who were treated with any type of FVIII concentrate and that included at least 25 patients with follow‐up were included in the analysis. Results Thirty‐three independent cohorts of PTPs with 4323 subjects and 43 incident de novo inhibitors were found and analyzed. The pooled incidence rate of inhibitor development for the 25 studies providing data on follow‐up was 3 (95% confidence interval 1–4) per 1000 person‐years. A significant association was not found between putative risk factors and inhibitor development in PTPs at meta‐regression analysis and subgroup analysis, but the model was sensitive enough to the inclusion of the reports on the Belgian‐Dutch experience with a highly immunogenic factor VIII. Conclusion We confirmed a low overall rate of de novo inhibitors in PTPs, without any significant effect of putative predictors, including the type of factor VIII concentrate.